1999
DOI: 10.1099/0022-1317-80-5-1231
|View full text |Cite
|
Sign up to set email alerts
|

A highly pathogenic simian/human immunodeficiency virus with genetic changes in cynomolgus monkey.

Abstract: A highly pathogenic simian/human immunodeficiency virus (SHIV), designated C2/1, was obtained by serum passages in cynomolgus monkeys of p-SHIV, an SHIV strain that contains the env gene of pathogenic human immunodeficiency virus type 1 89.6. CD4+ lymphocyte depletion was induced within 1 week of the SHIV-C2/1 infection in peripheral blood as well as in various lymphoid organs in all the animals tested, with symptoms of diarrhoea and no increase in body weight, followed by intense viraemia. Serum antibody agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 23 publications
3
62
0
Order By: Relevance
“…Therefore, simian/ human immunodeficiency viruses (SHIVs) constructed by inserting HIV-1 env, tat, vpu and rev into the SIV backbone have been developed to carry the antigenicity of HIV-1 Env into SIV (Shibata et al, 1991). Highly pathogenic SHIVs, which persistently infected rhesus macaques with a high set point following a high viral load peak, were obtained using in vivo adaptation to macaques (Reimann et al, 1996;Shinohara et al, 1999). As highly pathogenic SHIVs are useful in evaluating anti-HIV-1 neutralizing antibodies, SHIV-infected macaque models have been used in many preclinical investigations, even though SHIVs can also be used to evaluate cytotoxic Based on the Env features described above, to improve previously used SHIVs, we focused on two differences between HIV-1 initial clinical isolates and previously used SHIVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, simian/ human immunodeficiency viruses (SHIVs) constructed by inserting HIV-1 env, tat, vpu and rev into the SIV backbone have been developed to carry the antigenicity of HIV-1 Env into SIV (Shibata et al, 1991). Highly pathogenic SHIVs, which persistently infected rhesus macaques with a high set point following a high viral load peak, were obtained using in vivo adaptation to macaques (Reimann et al, 1996;Shinohara et al, 1999). As highly pathogenic SHIVs are useful in evaluating anti-HIV-1 neutralizing antibodies, SHIV-infected macaque models have been used in many preclinical investigations, even though SHIVs can also be used to evaluate cytotoxic Based on the Env features described above, to improve previously used SHIVs, we focused on two differences between HIV-1 initial clinical isolates and previously used SHIVs.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that generation of neutralization-resistant R5 tropic SHIV derived from SHIV-89.6 would be valuable with regard to comparing data between the virus and SHIV-89.6P. Hence, we generated SHIV-MK38 from SHIV-KS661, a derivative of SHIV-89.6, by introducing five amino acid substitutions in the V3 region to alter co-receptor use and two in vivo passages to adapt the virus to rhesus monkeys (Shinohara et al, 1999;Matsuda et al, 2010). SHIV-MK38 is R5 tropic and highly competent in replicating in rhesus macaques, and becomes neutralization resistant to autologous plasma in these SHIV-infected monkeys compared with the original SHIV-KS661 and SHIV-MK1, which are both the R5 virus prior to acclimation to monkeys .…”
Section: Introductionmentioning
confidence: 99%
“…Because SHIV89.6 does not induce both a marked decline in CD4 ϩ cells and a high level of plasma viral load in cynomolgus macaques, we passaged serum from virus-infected cynomolgus macaques. The variant was obtained by the serum passages using cynomolgus macaques inoculated with SHIV89.6, and it induced high levels of viremia (1-10 ϫ 10 7 viral RNA copies/ml) and marked CD4 ϩ T cell depletion (Ͻ10 cells/l) within 2 and 3 wk after viral inoculation (30,31,39). Furthermore, genomic study revealed 16 mutations of genomic DNA and 15 amino acid mutations in the Env region of parental virus.…”
Section: Discussionmentioning
confidence: 99%
“…After being immunized according to the protocol, animals were challenged with SHIV-C2/1 (30 -32), which was a SHIV-89.6 variant isolated at the peak of initial plasma viremia from an infected cynomolgus macaque (31). The original SHIV strain was provided by Dr. Y. Lu (Harvard AIDS Institute, Cambridge, MA) (33,34).…”
Section: Preparation Of Vaccine Ags and Challenge Virusmentioning
confidence: 99%
“…The SHIV-C2/1 stock comprised plasma obtained by serum passages of p-SHIV (derived from Fig. 1 SHIV-89.6) in cynomolgus monkeys (17)(18)(19). SHIVKS661c was propagated in CEMx174 cells and was confirmed to be genetically identical to the major sequences of the parent virus.…”
mentioning
confidence: 99%